Novel FSHβ gene SNPs correlation to litter size in Baladi and Zaraibi goats. (Journal of Basic and Applied Research in Biomedicine, 2022)
The objective of the present study is to identify the genetic polymorphism at two loci (exon1 and int2, exon3) in the FSHβ gene in two different Egyptian goat breeds (Baladi and Zaraibi goats) and their correlation with litter size. Using PCR- SSCP technique; 4 genotypes (AA, BB, CC and EE) were detected with the predominance of AA and CC genotype among the two breeds. Several SNPs were reported after sequencing in different genotypes. AA genotype had greater litter size in the two goat breeds. PCR- RFLP for int2, exon3 demonstrated the presence of 2 genotypes (MM and MS) in Baladi goats and only one genotype (MS) in Zaraibi does, with the predominance of MS genotype among the two breeds. One SNP; C 2526 G within the restriction site of the Mnl1 enzyme with no significant effect on litter size. These results revealed that exon1 and int2, exon3 of FSHβ gene could be used for improving breeding programs of goat.